Exocytosis of vacuolar apical compartment (VAC): a cell-cell contact controlled mechanism for the establishment of the apical plasma membrane domain in epithelial cells (The Rockefeller University Press, 1988)
The vacuolar apical compartment (VAC) is an organelle found in Madin- Darby canine kidney (MDCK) cells with incomplete intercellular contacts by incubation in 5 microM Ca++ and in cells without contacts (single cells in subconfluent culture); characteristically, it displays apical biochemical markers and microvilli and excludes basolateral markers (Vega-Salas, D. E., P. J. I. Salas, and E. Rodriguez-Boulan. 1987. J. Cell Biol. 104:1249-1259). The apical surface of cells kept under these culture conditions is immature, with reduced numbers of microvilli and decreased levels of an apical biochemical marker (184 kD), which is, however, still highly polarized (Vega-Salas, D. E., P. J. I. Salas, D. Gundersen, and E. Rodriguez-Boulan. 1987. J. Cell Biol. 104:905-916). We describe here the morphological stages of VAC exocytosis which ultimately lead to the establishment of a differentiated apical domain. Addition of 1.8 mM Ca++ to monolayers developed in 5 microM Ca++ causes the rapid (20-40 min) fusion of VACs with the plasma membrane and their accessibility to external antibodies, as demonstrated by immunofluorescence, immunoperoxidase EM, and RIA with antibodies against the 184-kD apical plasma membrane marker. Exocytosis occurs towards areas of cell-cell contact in the developing lateral surface where they form intercellular pockets; fusion images are always observed immediately adjacent to the incomplete junctional bands detected by the ZO-1 antibody (Stevenson, B. R., J. D. Siliciano, M. S. Mooseker, and D. A. Goodenough. 1986. J. Cell Biol. 103:755-766). Blocks of newly incorporated VAC microvilli and 184-kD protein progressively move from intercellular ("primitive" lateral) spaces towards the microvilli-poor free cell surface. The definitive lateral domain is sealed behind these blocks by the growing tight junctional fence. These results demonstrate a fundamental role of cell-cell contact-mediated VAC exocytosis in the establishment of epithelial surface polarity. Because isolated stages (intercellular pockets) of the stereotyped sequence of events triggered by the establishment of intercellular contacts in MDCK cells have been reported during normal differentiation of intestine epithelium (Colony, P. C., and M. R. Neutra. 1983. Dev. Biol. 97:349-363), we speculate that the mechanism we describe here plays an important role in the establishment of epithelial cell polarity in vivo.